2017
DOI: 10.5152/clinexphealthsci.2017.459
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Relation Between Attitudes Towards Gender Roles and Domestic Violence of Nursing And Paramedic Students

Abstract: Objective: The purpose of study was to assess the relation between attitudes towards gender roles and domestic violence of nursing and paramedic students in a country in the north east of our country. Methodology: A descriptive, cross-sectional study was used. The study population consisted of 205 nursing and paramedic students in 2014-2015 academic year. The sample consisted of 160 students. Data were collected with the "Demographic Information Form", "The Attitudes Towards Domestic Violence Scale (ATDV)", an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…In this study, it was determined that women adopted a more egalitarian perspective in terms of gender roles. Some studies support our findings (Bahadir Yilmaz & Öz, 2018; Unutkan et al, 2016; Utomo, 2016). However, there are studies that contradict our findings and show that male attitudes toward gender roles are more egalitarian (Direk & Irmak, 2017; Gecici et al, 2017).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In this study, it was determined that women adopted a more egalitarian perspective in terms of gender roles. Some studies support our findings (Bahadir Yilmaz & Öz, 2018; Unutkan et al, 2016; Utomo, 2016). However, there are studies that contradict our findings and show that male attitudes toward gender roles are more egalitarian (Direk & Irmak, 2017; Gecici et al, 2017).…”
Section: Discussionsupporting
confidence: 89%
“…In the study of Gecici et al conducted only with students studying health, the mean gender roles score was found as 112.42 ± 13.94. The mean score of gender roles in the study conducted by Bahadir Yilmaz and Öz (2018) with only nursing and paramedic students was found as 143.12 ± 20.98 (Bahadir Yilmaz & Öz, 2018; Gecici et al, 2017). Compared with these studies, it can be said that the students participating in the present study had higher scores and adopted a more egalitarian approach.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Therefore, it is of great importance that the beliefs and attitudes of male healthcare professionals including nurses about violence against women should be evaluated. Some research has explored the opinions of nursing students on violence against women (Akgun & Sahin, 2017; Bahadır Yýlmaz & Öz, 2018; Doran & Hutchinson, 2016; Khazaienejad et al., 2019; Rocha et al., 2015; Sabancıogulları et al., 2016; Silva et al., 2018; Sobrinho et al., 2019), but our search for studies in which the views of male nursing students about violence against women were investigated revealed a gap. However, such a study is important in terms of preserving and developing women's health and preventing the recurrence of problems through mitigating the risk factors of violence against women (Doran et al., 2019).…”
Section: Introductionmentioning
confidence: 99%